(1, 2)^-g-Homeomorphisms - A. Ponmalar; R. Asokan; O. Nethaji (International Journal of Mathematics And its Applications, 2021)
The purpose of this paper, we introduce the new types of functions called (1, 2)^-g-homeomorphisms and strongly (1, 2)^-g-homeomorphisms by using (1, 2)^-g-closed set prove that the collection of strongly (1, 2)^-g-homeomorphisms forms a group under the operations of composition functions.